Frequent Unrecognized Vertebral Fractures Associated with Increased Body Fat Mass in Children and Adolescents with Duchenne Muscular Dystrophy - Prasiw, Kanlaya; Khongkhatithum, Chaiyos; Fuangfa, Praman; Kositwattanarerk, Arpakorn; Mahachoklertwattana, Pat; Poomthavorn, Preamrudee (Neuropediatrics, 2024)
Objective Patients with Duchenne muscular dystrophy (DMD) have an increased risk of vertebral fractures (VFs). Ethnic variations may partly contribute to the fracture risk. This study aimed to demonstrate the VFs and body fat mass in Asian patients with DMD.Methods Demographic data and DMD-related parameters of the enrolled patients were collected. Lateral thoracolumbar spine radiographs were performed for VF assessment. The Genant classification was applied for VF severity grading (mild, moderate, and severe). Body composition analysis using dual-energy X-ray absorptiometry was performed. Serum calcium, phosphate, intact parathyroid hormone, and 25-hydroxyvitamin D concentrations were determined.Results There were 25 children and adolescents with DMD enrolled. The median (interquartile range [IQR]) age was 12.9 (9.6–19.3) years. Nine patients (36%) had VFs with a total of 31 sites of VFs (mild, N = 10; moderate, N = 3; and severe, N = 18). These VFs had never been recognized prior to this study. Comparing with the non-VF group, the VF group received a significantly greater cumulative prednisolone equivalent dose (1,258 [948–1,664] vs. 291 [17–823] mg/kg, p = 0.003). Body fat mass, represented by fat mass index and body fat percentage Z-scores, was greater in the VF group (2.46 [2.21–2.51] vs. 1.63 [0.36–2.07], p = 0.011 and 4.4 [3.1–5.5] vs. 1.8 [0.6–3.5], p = 0.008, respectively). No differences in serum calciotropic hormones and vitamin D status were demonstrated between patients with and without VFs.Conclusions VFs were frequent in patients with DMD. Patients with VFs had greater cumulative glucocorticoid dose and body fat mass than those without VFs.
Keywords: vertebral fracture; osteoporosis; Duchenne muscular dystrophy; glucocorticoid; body composition